Urgency of new regulatory on subsurface ownership and vertical depth boundaries in the national agrarian law: embracing Pancasila principles - Sukmaningsih, Ni Komang Irma Adi; Kusuma, Putu Riski Ananda (Jurnal Pendidikan PKN (Pancasila dan Kewarganegaraan), 2026)
This article examines the critical need for a Pancasila-oriented reconstruction of regulatory norms governing subsurface ownership and vertical land demarcation in Indonesia. Rapid urbanization and infrastructural development have exposed the inadequacy of the current two-dimensional land law framework, including the Basic Agrarian Law (UUPA) and Government Regulation No. 18/2021, which fail to provide measurable vertical boundaries, 3D cadastral registration, or clear allocation of underground space for public and private use. Using a normative juridical method with statutory, conceptual, and comparative approaches, the study identifies gaps in legal certainty, institutional harmonization, environmental protection, and the safeguarding of customary and indigenous communities. The findings highlight the urgent need to establish measurable vertical property boundaries, a functional 3D cadastre, a distinct Right to Subsurface Space, harmonized institutional authority, environmental and social safeguards, and specialized dispute resolution mechanisms. Anchoring these reforms within the principles of Pancasila ensures equitable justice, participatory governance, and sustainable urban development. The study concludes that modernizing subsurface property regulation is essential for legal certainty, inclusive development, and the realization of agrarian justice in Indonesia’s three-dimensional spatial era.